El autismo asociado a deficiencia intelectual moderada y su relaciòn con el aprendizaje de los niños y niñas que acuden a fundación orión de la ciudad de Ambato, provincia de Tungurahua”. Periodo junio 2013 a diciembre 2014. Lineamientos alternativos - Castillo Rivera, Leonela Alexandra (2015)
This research work, called "AUTISM ASSOCIATED WITH MODERATE INTELLECTUAL DEFICIENCY AND ITS RELATION TO THE LEARNING OF CHILDREN ATTENDING INTO ORION FOUNDATION IN AMBATO CITY, IN THE PROVINCE OF TUNGURAHUA It has been structured and developed in accordance with the Rules of Academic System of the National University of Loja. The central problem of the research is: What is the impact of moderate intellectual impairment in autism and its relation with learning children who are attending into Orion foundation of the city of Ambato, Tungurahua province? The overall objective was formulated: Determine Autism associated with moderate intellectual impairment and its relation with learning children that assist to foundation Orion. The central problem is in the intellectual impairment in children with autism. The methods used were: Scientific, Descriptive, Historical, Inductive and Statistical Model; The techniques used were as follows: A Test of Basic Concepts were applied to children with autism to assess mastery of basic, spatial, quantitative, ordinal and temporal concepts allowing indirectly assess the degree of cognitive and verbal child development and child. The survey, was applied to Orion´s teachers to assess whether the teachers are able to identify a real problem and work on it for inclusion. It is concluded that: 100% of teachers surveyed say YES that education is key to preparing teachers.100% agree that the contribution of the current government is GOOD as far as to delivery of materials to special schools for children with autism associated with moderate intellectual disability. On the other hand 100% respondents say YES that autism associated with a moderate intellectual disability affects inclusion of children that assist to Orion foundation. On the other hand 100% say that sometimes teachers care about children with autism who have a learning disability within the institution.100% of teachers say they do NOT work through an activity plan adapted to the educational needs to children with autism associated with moderate intellectual impairment. And finally 100% of the teachers said that YES it must be implemented within the institution an educational psychology department to assist in the learning problems of children who present autism associated with some form of intellectual deficiency. Basics test adapted to special education: allowed us to conclude that 61% of children with autism associated with moderate intellectual impairment gave positive answers;demonstrating a good level of learning and making them educable; while 39% showed a negative level in the development of its core functions, making them uneducable children.